Haikyu!! 26, Battle lines - Furudate, Haruichi, 1983- (VIZ Media LLC, 2018)
"Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? The practice game with Date Tech continues, and Karasuno clumsily dances around their new techniques in an attempt to break through the Iron Wall. But will any of these techniques work when even the Freak Quick can't? Then, time passes, the new year rolls around and the Spring Tournament begins!"--Page [4] of cover.